Heavy metals in water and trout from the fishing stations of the Apacheta River, Ayacucho - De La Cruz Palomino , Fortunato (2024)
The study addresses the relationship between heavy metals in the water that flows to fishing stations and the musculature of rainbow trout from the Hatumpampa, Qenhuacucho and Qorichallwa fishing stations, located at the foot of Apacheta-Vinchos (Huamanga region, Ayacucho); applied study of correlational descriptive scope, non-experimental and cross-sectional design; The population studied was made up of trout weighing 200 to 250 grams, and the waters of the Apacheta River, which feeds the fishing stations under study. For water analysis, three sampling points were established. As a result, it was found that the concentration of arsenic in the water exceeded the quality standards of the area for category 4 (E2), specified in the Supreme Decree of the Ministry of the Environment, No. 004-2017; Similarly, the arsenic content in trout muscle tissue exceeds the maximum allowable content set by the National Food Safety Standard and the Codex Commission of the People's Republic of China; On the other hand, the levels of cadmium, copper, chromium, mercury, nickel, lead, selenium and zinc are below the maximum permissible values in water and in the muscle tissue of trout. It is argued that there is a low correlation between the levels of heavy metals in the water and in the muscles of trout.